Fresno County DSS Director Ben Kelley Retirement Dinner at Holiday Inn - Watkins, Howard::::::::: (1989)
Centro La Familia and friends; includes Dan Fitzpatrick, Luisa Medina, Esther Padilla, Chris Peterson and Patience Milrod